The Influence of Reciprocal Teaching Style on Learning Outcomes Down Passing in Volleyball - Ahmad Muchlisin Natas Pasaribu; Nurkadri Nurkadri (Universitas PGRI Palembang, 2023)
The process of teaching and learning physical education is not so good, students feel bored in attending physical education lessons. So the purpose of this study is to obtain an overview of the differences between the independent variables and the dependent variable. This research design is a quantitative research with experimental methods. The population in this study were all fourth grade elementary school students in Bekasi City. From the results of the study it can be seen that tcount < ttable, -1.647 < 0.682 so it can be concluded that there is a significant influence between the reciprocal teaching style on the learning outcomes of volleyball underhand passing.